Innovative Strategies to Overcome Boredom in Islamic Religious Education at Islamic Boarding School-Based Vocational High Schools - Syaikhoni, Yusuf; Annur, Saipul; Karoma, Karoma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze and develop innovative strategies to overcome learning boredom in Islamic Religious Education subjects at Islamic boarding school-based vocational high schools (SMK). This study uses a qualitative approach with a case study method, conducted at SMK Islam Raden Fatah Darussalam Tugumulyo, Ogan Komering Ilir Regency, South Sumatra. The main data sources consisted of Islamic Religious Education teachers, 10th and 11th grade students, and pesantren administrators, while secondary data was obtained from school academic documents, pesantren activity schedules, and digital learning archives. Data collection techniques included participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted using the Miles and Huberman model through a process of data reduction, data presentation, and iterative conclusion drawing. The results of the study indicate that student learning fatigue is influenced by a heavy course load, an intensive boarding school schedule, monotonous teaching methods, and a lack of variety in digital media in Islamic Religious Education learning. Teachers implemented several innovative strategies such as project-based learning, gamification, contextual-collaborative approaches, and the use of interactive digital media in the form of reflective videos and online quizzes. These strategies have been proven to increase students' motivation, engagement, and reflective abilities regarding Islamic values. This research is significant because it provides practical contributions to boarding school-based schools in designing effective learning strategies to reduce boredom in Islamic Religious Education. Theoretically, this research enriches the study of Islamic Religious Education learning management, particularly in the context of vocational education integrated with the boarding school system.